Folk art and hybrid cultures: Cultural conversions in figurative pottery (Revista Internacional de Folkcomunicação, 2019)
The aim of this study is to analyze the process of cultural hybridization in the figurative ceramics of Alto do Moura in Caruaru, Pernambuco. Specifically, what we want to understand is the cultural reconversions that the descendants of Zé Caboclo's family have done over three generations, reconverting the codes of their culture, as popular culture, into the codes of mass culture, translated into the aesthetics of clay. The study was based on the use of oral history and combined data collection techniques such as field diary, semi-structured interview and systematic observation using photography as a record. In the course of the work it was observed that there is a reconversion of codes of the past, of memory, which usually hang around the rural or folkloric, in consumer objects that have an identity and aesthetic value by the consumer / collector. The reconversions observed in the pieces are of an identity nature, that is, reconstructing or rereading the past to enter or remain in the market, is what guarantees the sales and popular artist status to the oldest in the metier. Popular cultures; Hybridization; Cultural reconversion; Figurative ceramics.